Support to the Development of Legal and Institutional Frameworks on Access to Genetic Resources and related Benefit Sharing and Traditional Knowledge in line with the CBD and its Nagoya Protocol in Venezuela - Balcazar, Isabel (2025)
In collaboration with the United Nations Environment Programme (UNEP), Ministry of People’s Power for Ecosocialism (MINEC), United Nations Development Programme (UNDP), Agronomy Faculty of the Central University of Venezuela (UCV-FAGRO) and the Inter-American Institute for Cooperation on Agriculture (IICA)